Safety and efficacy of verinurad, a selective URAT1 inhibitor, for the treatment of patients with gout and/or asymptomatic hyperuricemia in the United States and Japan: Findings from two phase II trials. Issue 6 (2nd November 2019) - Fitz-Patrick, David; Roberson, Kent; Niwa, Kiyoshi; Fujimura, Takabumi; Mori, Koji; Hall, Jesse; Yan, Xiaohong; Shen, Zancong; Liu, Sha; Ito, Yasushi; Baumgartner, Scott
Abstract: Objective: Evaluate efficacy/safety of verinurad monotherapy in patients with gout (Japan/US) or asymptomatic hyperuricemia (Japan). Methods: Two randomized, placebo-controlled, phase II studies were conducted (NCT01927198/NCT02078219). Patients were randomized to once-daily doses of placebo or escalating doses of verinurad (study 1: 5–12.5 mg; study 2: 2.5–15 mg). Primary endpoint was percentage change from baseline in serum urate (sUA) at week 12 (study 1)/week 16 (study 2). Safety was also assessed. Results: Most patients in study 1 ( n = 171) were white (74.9%); all patients were Japanese in study 2 ( n = 204). Least squares means (±SE) estimate of percentage change in sUA levels from baseline in study 1 was 1.2 ± 2.9 for placebo, and –17.5 ± 2.8, –29.1 ± 2.8, –34.4 ± 2.9 for verinurad 5, 10, 12.5 mg, respectively. In study 2, results were –2.4 ± 2.5 and –31.7 ± 2.5, –51.7 ± 2.6, –55.8 ± 2.5, respectively. Difference from placebo was significant for each verinurad dose ( p <.0001). The proportion of patients with treatment-emergent adverse events (TEAEs) was similar across all groups. Renal-related TEAEs were more common with verinurad than placebo. Conclusion: Verinurad monotherapy resulted in sustained reductions in sUA in Japanese/US patients but renal AEs occurred, so verinurad alone is not recommended for treatment of hyperuricemia or gout. The renal consequences of excessive uric acid excretion deserve study.